Answer:
y=-3
Step-by-step explanation:
[1] x = 2y + 4z + 26
// Plug this in for variable x in equation [2]
[2] 4•(2y+4z+26) - 2y + 4z = 6
[2] 6y + 20z = -98
// Plug this in for variable x in equation [3]
[3] 2•(2y+4z+26) + 2y - z = 6
[3] 6y + 7z = -46
// Solve equation [3] for the variable z
[3] 7z = -6y - 46
[3] z = -6y/7 - 46/7
// Plug this in for variable z in equation [2]
[2] 6y + 20•(-6y/7-46/7) = -98
[2] - 78y/7 = 234/7
[2] - 78y = 234
// Solve equation [2] for the variable y
[2] 78y = - 234
[2] y = - 3